INVESTIGATING THE ROLE OF COMMUNITY ENGAGEMENT IN ENHANCING CHILDREN'S SAFETY IN PUBLIC HIGH-RISE RESIDENTIAL ENVIRONMENTS IN SOUTHWEST NIGERIA - BREAKTHROUGH MAURICE CHINEDU UKAOHA; ANTHONY CHUCKS OKEIBUNOR IWEKA; KAYODE ANTHONY ADEBAYO (International Journal of Earth Design and Innovation Research, 2026)
Ensuring children's safety in public high-rise residential environments is a pressing concern in Southwest Nigeria. Previous studies highlighted the significance of community engagement and safety measures in promoting children's well-being, yet gaps persisted in understanding their implementation in Nigerian contexts. This study examined children's safety measures and community engagement interventions in public high-rise residential environments, building on literature emphasizing the role of social cohesion and participatory approaches. A mixed-methods approach was employed, combining surveys, interviews, and observations in five locations: Marina Towers, Lagos; Lekki Towers, Lagos; Bodija Estate, Oyo; Ogun State Housing Estate, Ogun; and Osun State Housing Estate, Osun. Findings revealed varying levels of attention to safety measures and community engagement, with Bodija Estate, Oyo, and reporting higher attention (70%) compared to Osun State Housing Estate, Osun (40%). The study underscored the importance of community engagement and safety measures like safety gates and regular inspections in promoting children's safety. Recommendations included increasing community engagement and fostering social cohesion through community events to enhance safety outcomes.